Influence of the KCl spraying addition on the leaves at different stages on some physiological and chemical indexes of the KT3 potato cultivar - Dinh, Nguyen Van (Academia Journal of Biology, 2014)
The KT3 potato cultivar was a hybrid (Serrana x I.1035) from the International Potato Center (CIP) and had some agricutural characteristics: stem tall to medium; stems semi- erect, large to medium; dark green to green leaves; yield hight to good; resistant to virus and to leaf bright. The KT3 potato cultivar was cultivated at the Vinhphuc province from October 20 of 2003 to January 20 of 2004. We have sprayed KCl 0.2% additionally on the leaves at different growth stages (15 days, 30 days, 15 & 30 days after cultivation). Then, we studied the influences of this fertilizer on some physiological and biochemical indexes after 40; 50; and 60 treatment days . The study has proved that the KCl spraying addition after 30 days has had the highest fluorescence and increased the dry matter from 107.8% to 112.5% compared to those without KCl 0.2% sprayed on leaves. The treatment with KCl 0.2% at different growth stages has inceased the number of tubers/clump, the weight of tubers/clump and the tuber yield from 103.76% to 107.18%. Especially, the highest yield was recorded with the spraying after 30 days (107.18%). It did not change the total contents of maltose, proteins, ascorbic acid but increased the total contents of starch from 105.21% to 109.95% compared to those without KCl 0.2% sprayed on leaves.